Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Pacific Northwest)--Olympia oyster - Couch, David (U.S. Department of the Interior, 1989)
U.S. Fish. Wildl. Serv. Biol. Rep. 82(11.124)